A State of De-Stress: Examining the Relationship Between Subjective Well-Being, Self-Compassion, and Empathy - Hablado, Kurt; Clark, Mitchell (Advances in Social Sciences Research Journal, 2020)
University can be a period of stress caused by academic, social, or personal demands. Yet most are able to rise above the adversity and grow from their experiences. Research on stress has found that a negative association exists with subjective well-being broadly conceptualized as life happiness (Denovan & Macaskill, 2017; Zhang, 2009). There are also positive relationships demonstrated between self-compassion and empathy with subjective well-being (Bluth et al., 2016; Thomas et al., 2007). This study examined the relationship between perceived stress and subjective well-being in a non-clinical university population. The study also examined the relationship between stress and subjective well-being, and how that relationship was moderated by the self-compassion and mediated by empathy.